2021
DOI: 10.3390/mi12111331
|View full text |Cite
|
Sign up to set email alerts
|

Dual Laser Beam Asynchronous Dicing of 4H-SiC Wafer

Abstract: SiC wafers, due to their hardness and brittleness, suffer from a low feed rate and a high failure rate during the dicing process. In this study, a novel dual laser beam asynchronous dicing method (DBAD) is proposed to improve the cutting quality of SiC wafers, where a pulsed laser is firstly used to introduce several layers of micro-cracks inside the wafer, along the designed dicing line, then a continuous wave (CW) laser is used to generate thermal stress around cracks, and, finally, the wafer is separated. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…A thin damage layer is thus created inside the semiconductor single crystal by the ultrafast laser writing throughout the surface of the semiconductor. [14][15][16] The slicing of semiconductor wafers can be realized by exfoliating the damage layer from the perfect single-crystal region via mechanical stress, swelling stress, or thermal stress. [9,17,18] By replacing wire sawing with ultrafast laser slicing, the material loss and slicing duration per wafer are significantly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…A thin damage layer is thus created inside the semiconductor single crystal by the ultrafast laser writing throughout the surface of the semiconductor. [14][15][16] The slicing of semiconductor wafers can be realized by exfoliating the damage layer from the perfect single-crystal region via mechanical stress, swelling stress, or thermal stress. [9,17,18] By replacing wire sawing with ultrafast laser slicing, the material loss and slicing duration per wafer are significantly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Amit Yadav et al [ 21 ] have investigated the SD of sapphire wafers with near-infrared femtosecond pulses to leave a high-quality surface, and Caterina Gaudiuso et al [ 22 ] applied a femtosecond laser to SD on quartz glass. Zhang et al [ 23 ] proposed a new asynchronous double-beam laser SD method, in which an ultrafast laser is focused inside of the SiC wafer along the writing line to form microcracks, heated by continuous lasering to expand the cracks through thermal stress, achieving the dicing of a 200 μm SiC wafer with almost no damage to the kerf. However, it is only suitable for thicknesses less than 200 µm.…”
Section: Introductionmentioning
confidence: 99%
“…Caterina G. et al 23 reported a one-step method cutting the quartz with femtosecond laser SD, and studied the influence of relevant parameter on processing. Zhang et al 24 reported an asynchronous double-beam laser SD method, which includes SD process with pulse laser and split process with continuous laser. Nevertheless, cost and stability are the issue that have to be considered in industrial manufacture yet.…”
mentioning
confidence: 99%